2020
DOI: 10.3389/fmicb.2019.02953
|View full text |Cite
|
Sign up to set email alerts
|

High Diversity and Functional Complementation of Alimentary Canal Microbiota Ensure Small Brown Planthopper to Adapt Different Biogeographic Environments

Abstract: Almost all insects harbor commensal bacteria in the alimentary canal lumen or within cells and often play a pivotal role in their host's development, evolution, and environmental adaptation. However, little is known about the alimentary canal microbiota and their functions in sap-sucking insect pests of crops, which can damage plants by removing plant sap and by transmitting various plant viruses, especially in the small brown planthopper, Laodelphax striatellus. In this study, we characterized the alimentary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Prior studies have also highlighted that the composition of microbial communities in insects can be influenced heavily by the external environment, in which the abundance and composition of intestinal microbes often represent the insect's living environment (Koskinioti et al, 2019;Liu et al, 2020;Wang et al, 2019). Insects are small heterotherm, and the external environment has a great influence on their life activities (Guedot et al, 2018;Zhu et al, 2006).…”
mentioning
confidence: 99%
“…Prior studies have also highlighted that the composition of microbial communities in insects can be influenced heavily by the external environment, in which the abundance and composition of intestinal microbes often represent the insect's living environment (Koskinioti et al, 2019;Liu et al, 2020;Wang et al, 2019). Insects are small heterotherm, and the external environment has a great influence on their life activities (Guedot et al, 2018;Zhu et al, 2006).…”
mentioning
confidence: 99%
“…(c) Global climate warming, organic farming methods to reduce the use of pesticides, and the commercialization of genetically modified crops that are resistant to lepidopterans or beetles may indirectly lead to the changes of planthopper population and the outbreaks of fijiviruses. Similar works have been done for other virus-vector insect systems (Wei and Li, 2016;Qin et al, 2018;Wang et al, 2019;Liu et al, 2020), but whether these results also apply to fijiviruses and their vector insects needs to be determined.…”
Section: Concluding Remarks and Prospectsmentioning
confidence: 80%
“…On the contrary, acquisition and transmission of tomato yellow leaf curl virus by Bemisia tabaci were significantly enhanced by Rickettsia (Kliot et al, 2014). Moreover, the microbiota might contribute to the higher fecundity of L. striatellus, which in turn may be associated with the outbreaks of the virus (Liu et al, 2020). Besides microbes in vector insects, some insect-specific viruses have also been found in L. striatellus or S. furcifera (Wu et al, 2018(Wu et al, , 2019.…”
Section: Insect Microbesmentioning
confidence: 99%
“…To better understand the complex disease system and provide an accurate forecast to guide control measures, we believe that future research should focus on, but not be limited to, the following areas. been done for other virus-vector insect combinations (Wei and Li, 2016;Qin et al, 2018;Wang et al, 2019a,b;Liu et al, 2020), but the results for these systems need to be confirmed and compared with those for RBSDV and SBPHs.…”
Section: Future Pros Pec Tsmentioning
confidence: 99%